The dare - Preston, Natasha (New York : Delacorte Press, 2024)
When a high school prank turns deadly, Marley and her friends must do everything they can to conceal the truth.
Includes an excerpt from The Haunting.
Ages 12 and up.
Keywords: Practical jokes -- Fiction; Traffic accidents -- Fiction; Friendship -- Fiction; Thrillers (Fiction)